Last Night. Oratorios, Theatre Royal, Drury-Lane, Wednesday, March 26, 1817 - Theatre Royal, Drury Lane (London, England):::Creator:::::::::::: (Theatre Royal ; Lowndes, printer; London, 2020)
Handbill listing works to be performed at the Theatre Royal, Drury-Lane, London, on March 26, 1817 with names of performances. Included a "grand selection" of works by Handel, Haydn, Mozart, and Beethoven's Wellingtons Victory, op. 91, the last performance of that work in the season.